HUBUNGAN ANTARA MENYUSUI EKSKLUSIF DENGAN DURASI AMENOREA LAKTASI DI PMB HUSNIYATI - Saswita, Reni; Elsira, Noviani; Enggelina, Nadia (Jurnal Kesehatan dan Pembangunan, 2025)
Breastfeeding is the most natural and ideal way to provide nutrition to babies. Apart from babies, exclusive breastfeeding (6 months) also provides benefits for mothers, namely that it can influence the duration of amenorrhea. Exclusive breastfeeding has a significant impact on the duration of lactational amenorrhea. The aim of this study was to analyze the relationship between exclusive breastfeeding and the duration of lactational amenorrhea in PMB Husniyati. The research method uses quantitative analytical methods with a cross sectional approach. The population in the study were all mothers who exclusively breastfed who visited PMB Huniyati Palembang with a total sample of 36 respondents taken using the purposive sampling method. The research results showed that the frequency distribution of respondents who experienced amenorrhea with a duration of > 6 months was 21 respondents (58.3%), 26 respondents who exclusively breastfed (72.2%). The results of statistical tests showed that there was a significant relationship between exclusive breastfeeding and the duration of lactational amenorrhea at PMB Husniyati Palembang in 2025 (p.value = 0.007). It is hoped that the suggestions can further increase the promotion of the use of lactational amenorrhea contraception to postpartum mothers because apart from increasing exclusive breastfeeding, it can also delay pregnancy.